MENDESAIN PEMBELAJARAN TEMATIK-INTEGRATIF BERPANDUKAN PRANADA KUNCI G - SUDIRMAN SUDIRMAN (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2022)
Designing learning is very important as a guide of learning implementation effectively and efficiently. The competency-based 2013 Curriculum and the 2022 Merdeka Curriculum implementation need to be designed comprehensively. However, empirically designing such learning specifically is still limited. This study aims to determine whether the use of the Pranada Kunci G (PK-G) model can improve teachers’ ability in designing of Thematic-Integrative Learning (TIL). The type of research is an experimental design of One Group Pretest Posttest Study. There were nine respondents were selected purposively. Data were obtained through tests before and after treatment which were strengthened by information from unstructured interviews. Data were analyzed using percentages which were reviewed qualitatively. The treatment was carried out three times which showed an increase in the score. On average, respondents' test results were 2.77 (0-4), with a moderate position approaching the good category (70-85%). This achievement means that the use of PK-G can made teachers easier to TIL design. The conclusion is, if the teacher designs TIL using of the PK-G model, the thematic learning design is more integrated and comprehensive. ABSTRAKMendesain pembelajaran sangat penting sebagai pemberi arah pelaksanaan pembelajaran secara efektif dan efisien. Implementasi Kurikulum 2013 dan Kurikulum Merdeka 2022 yang berbasis kompetensi perlu didesain secara komprehensif. Namun, secara empiris mendesain pembelajaran seperti itu secara spesifik masih sangat terbatas. Penelitian ini bertujuan untuk mengetahui apakah penggunaan model Pranada Kunci G (PK-G) dapat kemampuan guru mendesain pembelajaran tematik-integratif (PTI) . dalam Jenis penelitian adalah eksperimen desain One Group Pretest Postest Study. Sebanyak sembilan orang responden yang dipilih secara purposive. Data diperoleh melalui tes sebelum dan setelah treatmen yang diperkuat dengan informasi hasil wawancara takberstruktur. Data dianalisis menggunakan persentase yang diulas secara kualitatif. Treatmen dilakukan tiga kali yang menunjukkan terdapat peningkatan skor. Secara rata-rata, hasil tes responden adalah 2.77 (0-4), dengan posisi sedang mendekati kategori baik (70-85%). Capaian ini berarti penggunaan PK-G dapat memudahkan guru mendesain PTI. Kesimpulannya adalah apabila guru mendesain PTI dengan menggunakan model PK-G, maka desain pembelajaran tematik menjadi lebih terintegrasi dan komprehensif.